PROSES PENGOLAHAN PASCA PANEN BUAH MARKISA BERNUTRISI TINGGI - Rahayu, Mudji; Qomaruddin, ' (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
The purpose of Science, technology, dam art for Society are to (1) build skilled and professional Buring society in planting passion fruit; (2) to produce high quality, high quality juice, syrup and dodol passion fruit; (3) building entrepreneur spirit and improving economy of Buring society through passion cultivation, and (4) creation of Micro small and Medium Enterprises in Buring Area. To achieve these objectives, there will be activities such as: (1) counseling of planters, fertilizers, and maintenance of passion fruit trees; (2) training of juice making, syrup and passion fruit dodol; and (3) socialization and training on how to market products produced from passion fruit either directly with consumers or online. The results achieved are; (1) Many farmer groups in RW.02 and Rw.08 Buring village planted passion fruit, (2) producing juice, syrup, and passion fruit dodol, (3) society of Buring understand the marketing of passion fruit and processed products from passion fruit